Legal Protection for Eco-Friendly Product Consumer Losses Due to the Practice of Greenwashing - Balqis, Tazkia; Widiyanti, Ikarini Dani; Zulaika, Emi (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2023)
This research refers in connection to the high tendency of demand for green products which has led some business actors that carry out covert promotions to deceive green consumers through false claims of being environmentally friendly where the implementation is contrary to Law Number 8 of 1999 about Consumer Protection in Indonesia and strategic policies regarding realized by the Government of Indonesia through the RPJMN 2005-2025 about Sustainable Consumption and Production (SCP). This article will discuss legal protection arrangements for eco-friendly product consumers and identify the losses and responsibilities of business actors who have carried out greenwashing practices toward green consumers based on doctrinal research (normative juridical) with a statutory and conceptual approach. The purpose of this article is to find out the norms of legal protection for green consumers and increase awareness about the practice of greenwashing. The findings showed the losses experienced by green consumers as a result of greenwashing are material and immaterial costs, while the existence of green consumers is protected by environmental protection and management law, consumer protection law, and eco-label policy.